Design and analysis of 4x4 smith waterman's based DNA alignment accelerator using multicore architecture - Mohd Najib, Nur Fariza (2011)
This paper presents the design and analysis of 4x4 Smith Waterman’s based DNA sequences alignment accelerator using multicore architecture. The first objective of this paper is to design 4 x 4 matrix filling module of DNA sequence alignment accelerator. The second objective is to combine matrix filling module with traceback and reconstruction module design by previous student in order to create single core. The third objective is to construct modules that consist of 2, 4 and 8 cores. The fourth objective is to simulate and verify the functionality of the new matrix filing, single and multicore modules on Xilinx FPGA design flow. The last objective is to verify, optimize and analyze the multicore modules using VCS, DC, ICC and PT. This paper focuses on the timing analysis, power and area of multicores architecture using Smith-Waterman algorithm. To achieve a higher performance with low latency and high throughput data has become a serious concern for today’s DNA laboratory as the increase of number of DNA database all around the world. Researchers may have done different kind of architecture such as pipeline, vector, multicycle to boost up the speed performance of DNA sequences alignment. All design is written in Verilog language and the result is verified on Synopsys EDA tool which are Verilog Compiler Simulator (VCS), Design Compiler (DC) and ICCompiler (ICC).